Assessing the Discriminative Ability and Internal Consistency of the School Outcomes Measure. (4th April 2013) - Arnold, Sandra H.; Kolobe, Thubi H. A.; Thompson, David M.; Boeckman, Lindsay
Abstract : The School Outcomes Measure (SOM) measures the outcomes of students who receive school-based occupational and physical therapies in the USA. This study examined the SOM's discriminative ability and internal consistency. Descriptive data from a previous study of 73 students, classified by gross motor function classification (GMFCS) level of disability, was computed to determine the frequency of use of the SOM items and differences in subscale scores by students with various ages and levels of disability. There were no differences in mean subscale scores based on age; however students with less severe disabilities (GMFCS I–III) had higher mean scores in all subscales except expresses learning all students and behavior. Cronbach's alpha coefficient was used to examine the internal consistency of items of the SOM. The correlations between many of the items within the subscales were high (.87–.99). Lower alpha coefficients were noted when the SOM was applied to students in GMFCS Levels II and III on two subscales when compared to GMFCS Levels I, IV, and V. On the basis of this evaluation, we revised the SOM to prepare it for a national field testing to measure its construct validity.